A STUDY ON AWARENESS OF EMPLOYEE EXCELLENCE IN NATIONALISED BANKS WITH SPECIAL REFERENCE TO PERAMBALUR DISTRICT - Mr. A. Arun Prassad, Dr. S. Parithi (International Journal of Advanced Science and Technology, 2020)
Excellence in modern human resource management is the prerequisite that makes the modern banks to be successful in this highly competitive environment. As banks are purely service-based organizations, the productivity and achievement of the banks are purely based on the employees working in the banks. The Banks always search for excellent human resources for recruitment but the utilization of the expertise after selection is always a question. This research strives to focus on the awareness of employee excellence in Nationalised Banks with special reference to the Perambalur District. It also focuses on the importance of employee excellence in banks.